Local Economic Retention in Bali Tourism: the Role of Community-Based Tourism in Reducing Economic Leakage - Vivi Vivi; Jery Christianto; Rina Hartanti (CV. Ulil Albab Corp, 2026)
study examines the issue of local economic retention in Bali’s tourism sector, focusing on the role of Community-Based Tourism (CBT) in reducing economic leakage. Although tourism significantly contributes to regional economic growth, a substantial portion of its benefits does not remain within the local economy due to weak economic linkages, reliance on external supply chains, and foreign ownership structures. This research aims to develop an integrated conceptual framework that explains how structural factors namely economic linkages, infrastructure, and destination specialization interact with CBT as a mediating mechanism to enhance local economic retention. The study employs a conceptual qualitative approach using secondary data analysis, synthesizing empirical findings, macroeconomic data, and theoretical perspectives. The findings indicate that while infrastructure development and specialization drive tourism growth, they do not automatically ensure equitable benefit distribution. CBT plays a crucial role in strengthening local participation, promoting local ownership, and enhancing value capture within the community. However, its effectiveness depends on institutional capacity and governance quality. This study highlights the importance of shifting from growth-oriented tourism to a retention-based development approach to achieve more inclusive and sustainable outcomes.